2014
DOI: 10.4236/aim.2014.413099
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Evaluation of Test Strips for Anti-Ganglioside Antibodies in Patients with Guillain-Barré Syndrome Using EUROLineScan Software

Abstract: Campylobacter jejuni infection has been implicated in the pathogenesis of Guillain-Barré syndrome (GBS) due to production of humoral immune response against neural antigens. A case-control study was performed in a tertiary care teaching hospital for the estimation of anti-ganglioside antibodies in GBS patients and their controls. Blood samples were collected from 59 GBS cases, 58 neurological controls (NC) and 60 non-neurological control (NNC) patients for automatic estimation of IgG and IgM antibodies to seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…[22] Sharma et al studied the relationship between preceding C. jejuni infection and its correlation to the various subtypes of GBS by electrophysiological and serological testing. They found that preceding C. jejuni infection is common among GBS patients and is often associated with the axonal variety, which is generally present in a younger age group as compared to patients with AIDP (acute inflammatory demyelinating polyneuro- [23,24] pathy). Vaishnavi et al reported a case-control study for the estimation of anti-ganglioside antibodies in GBS patients (n=59) and their neurological (n=58) and nonneurological controls (n=60) by both subjective and automatic estimation of IgG and IgM antibodies to seven gangliosides using EUROLineScan software.…”
Section: Introductionmentioning
confidence: 99%
“…[22] Sharma et al studied the relationship between preceding C. jejuni infection and its correlation to the various subtypes of GBS by electrophysiological and serological testing. They found that preceding C. jejuni infection is common among GBS patients and is often associated with the axonal variety, which is generally present in a younger age group as compared to patients with AIDP (acute inflammatory demyelinating polyneuro- [23,24] pathy). Vaishnavi et al reported a case-control study for the estimation of anti-ganglioside antibodies in GBS patients (n=59) and their neurological (n=58) and nonneurological controls (n=60) by both subjective and automatic estimation of IgG and IgM antibodies to seven gangliosides using EUROLineScan software.…”
Section: Introductionmentioning
confidence: 99%